Toward a new conceptualization of resilience at work as a meta-construct? - Galy, Anaïs; Chênevert, Denis; Fouquereau, Evelyne; Groulx, Patrick (Frontiers in Psychology, 2023)
Organizations of all kinds are faced with multiple demands for adaptation of increasing frequency and amplitude due to such factors as reorganizations, climate change, pandemics, and labor shortages. This new reality requires our organizations to anticipate, adjust, and demonstrate resilience. The study of resilience at work relies on the comprehension of how organizational systems, as well as their work collectives and members, manage to overcome adversity without suffering from irreversible damage. However, the study of this phenomenon of interest contains grey areas concerning both its definition, its conceptualization, and the dynamic processes that underlie it. This theoretical paper addresses these different issues by providing first, a conceptual content analysis of the most frequently used definitions and second, a new conceptualization of resilience at work as a resource, either individual or collective. Moreover, we suggest a multilevel, dynamic, and virtuous conceptual approach to resilience at work, relying on both bottom-up and top–down flows. Accordingly, we formulate different theoretical propositions upon which future empirical research can draw to analyze the relationships between individual, team, and organizational resilience. Building on a conservation of resources lens, we offer a novel contribution to the resilience in the workplace literature, by providing an integrative and multilevel theory of resilience at work that highlights both the processual and interpersonal nature of its emergence, and the organizational levers that can foster it.